Systems for planning and control in manufacturing : systems and management for competitive manufacture - Harrison, David K. (IIE textbook series., 2002)
The book is divided into two sections:Section 1 - Introduces the subject as a whole and describes the key generic tools and techniques to support the manufacturing organisation. Section 2 - Modern planning and control methods at a detailed level.*Each chapter begins with a summary of key points and objectives to aid learning*Case studies included throughout to illustrate the key elements of the text in a practical context*Introduces a range of systems and management topics supported by examples and case studies.